Returns to education in Colombia: Impact of human capital in times of change - Rodríguez, Dustin Tahisin Gómez (Edelweiss Applied Science and Technology, 2024)
The general objective of the article is to critically examine the application of Human Capital Theory and assess the returns to education for economists, accountants, and business administrators in the Colombian context, specifically during and after the COVID-19 pandemic. The methodology employed is quantitative, utilizing a micro-econometric model based on Mincerian equations, analyzing data from the Gran Encuesta Integrada de Hogares (GEIH) of DANE for the years 2018, 2019, 2021, and 2022. The main findings indicate that investment in education is revealed as an essential strategy to optimize human capital, promote economic development, and contribute to overall well-being in a dynamic and challenging economic environment. Additionally, it is concluded that the returns to education for Colombian economists are higher than those of other professions, evidencing a gender bias in remuneration. These results underscore the importance of education in the socio-economic resilience of the country.